Strategi pengembangan Desa Banjarasi menjadi destinasi wisata berkelanjutan - Sutrisno, Eko Yuli; Endyana, Cipta; Hadian, Mohamad Sapari Dwi (Universitas Negeri Malang, 2025)
Development strategy for Banjarasi Village as a sustainable tourism destination This research was conducted in Banjarasri Village, Kalibawang, Kulon Progo, Special Region of Yogyakarta. The background of this study is that Banjarasri Village has not yet become a popular tourist destination, even though several surrounding villages have already gained recognition as attractive tourist destinations. The purpose of this study is to identify the strategic position of Banjarasri Village and recommend strategies for developing it into a sustainable tourism destination. The research method employed is descriptive qualitative. Data collection techniques include observation, interviews, and documentation. Data analysis was carried out through data reduction, data presentation, and drawing conclusions. The findings indicate that Banjarasri Village has the potential to become a sustainable tourism destination. The recommended strategies for development are maximizing the village’s strengths by building tourism facilities and infrastructure, creating scenic viewing spots, developing heritage and educational tourism packages, projecting the merti dusun tradition as a cultural tourism attraction, and promoting the village’s tourism potential. The second strategy is minimizing weaknesses to seize opportunities, such as developing glamour camping (glamping), establishing traditional village-style eateries, and forming a tourism awareness group. The third strategy is utilizing strengths to address threats, including campaigning that Banjarasri’s attractions are located in a safe zone from Mount Merapi’s disaster risk, improving attraction quality, and implementing product differentiation. The fourth strategy is reducing weaknesses to prevent threats by providing affordable and easily accessible accommodation, offering dining options that meet tourists’ preferences, and conducting education and training programs in the tourism sector. Penelitian ini dilakukan di Desa Banjarasri, Kalibawang, Kulon Progo, Daerah Istimewa Yogyakarta. Latar belakang dilakukannya penelitian ini adalah Desa Banjarasri belum menjadi destinasi wisata yang ramai dikunjungi wisatawan padahal beberapa desa yang berada di sekitarnya saat ini telah menjadi destinasi wisata yang digemari wisatawan. Tujuan penelitian ini adalah untuk mengetahui posisi strategis Desa Banjarasri dan rekomendasi strategi yang dapat digunakan untuk mengembangkan Desa Banjarasri menjadi destinasi wisata berkelanjutan. Metode yang digunakan adalah deskriptif kualitatif. Teknik pengumpulan data yang digunakan adalah observasi, wawancara, dan dokumentasi. Analisis data dilakukan dengan reduksi data, penyajian data, dan penarikan kesimpulan. Adapun hasil penelitiannya adalah Desa Banjarasri memiliki potensi untuk menjadi destinasi wisata berkelanjutan. Saran rumusan strategi yang dapat diterapkan untuk pengembangan Desa Banjarasri adalah memaksimalkan kekuatan Desa Banjarasri dengan membangun sarana dan prasarana wisata, membangun spot untuk menikmati pemandangan, membuat paket wisata heritage dan pendidikan, memproyeksikan kegiatan merti dusun menjadi daya tarik wisata budaya, dan melakukan promosi daya tarik wisata Desa Banjarasri. Strategi yang kedua adalah mengurangi kelemahan untuk meraih peluang yang dapat dilakukan dengan membangun glamour camping (glamping), membangun tempat makan khas pedesaan, dan membentuk kelompok sadar wisata. Strategi yang ketiga adalah memanfaatkan kekuatan untuk menghadapi ancaman, yaitu dengan mengkampanyekan bahwa daya tarik Desa Banjarasri berada di zona aman bencana Gunung Merapi, meningkatkan kualitas daya tarik, dan melakukan diferensiasi produk. Strategi yang keempat adalah mengurangi kelemahan untuk mencegah ancaman dengan menyediakan akomodasi penginapan yang terjangkau dan mudah dipesan, menyediakan tempat makan yang sesuai dengan kebutuhan dan keinginan wisatawan, dan mengadakan program Pendidikan dan pelatihan bidang pariwisata.